COMPARISON OF THE EFFICACY OF SILDENAFIL ALONE VERSUS SILDENAFIL PLUS BOSENTAN IN NEWBORNS WITH PERSISTENT PULMONARY HYPERTENSION - Fatima, Nazia; Arshad, Sohail; Quddusi, Ahmad Iqbal; Rehman, Abdur; Nadeem, Aashee; iqbal, imran (Journal of Ayub Medical College Abbottabad, 2018)
Background: Persistent pulmonary hypertension is a serious disease among new-borns. Inhaled nitric oxide is first line of therapy along with extracorporeal membrane oxygenation. Pulmonary vasodilators such as sildenafil, bosentan and milrinone are also used to treat persistent pulmonary hypertension especially in resource limited centres where inhaled nitric oxide is not available. The objective of this study was to compare the effect of sildenafil alone and sildenafil with bosentan on severity of tricuspid regurgitation and duration of hospitalization in new-borns with persistent pulmonary hypertension. Methods: This was single blinded clinical trial conducted at The Children's Hospital & the Institute of Child Health, Multan, Pakistan, from July 2016 to December 2016. New-borns with pulmonary hypertension were admitted and divided into two groups. Group A was treated with sildenafil (2mg per kg per dose three times a day) and group B with both sildenafil (2 mg per kg per dose three times a day) and bosentan (1 mg per kg per dose twice a day). Results: There were 50 new-borns in each group. The mean age, sex distribution and baseline TR measurement (mmHg) at the time of admission was similar in both the groups. Measurement of TR (mmHg) after 72 hours admission was significantly less in Group B as compared to group A (11±4.62 versus 23±4.78), p value<0.0001. The mean duration of hospital stays (days) was 10.12±5.20 in group A and 7.56±3.77 in group B (p-value <0.0001). There was no mortality in any group and no case of hypotension in both groups. Conclusion: The combined use of sildenafil and bosentan is more effective than sildenafil alone for control of pulmonary hypertension in resource limited centres. Keywords: Persistent pulmonary hypertension; sildenafil; bosentan; echocardiography